Respiratory complications after surgery in Vietnam: National estimates of the economic burden - Hanh, Bui My (Lancet Reg Health West Pac, 2021)
BACKGROUND: Estimating the cost of postoperative respiratory complications is crucial in developing appropriate strategies to mitigate the global and national economic burden. However, systematic analysis of the economic burden in low- and middle-income countries is lacking. METHODS: We used the nationwide database of the Vietnam Social Insurance agency and extracted data from January 2017 to September 2018. The data contain 1 241 893 surgical patients undergoing one of seven types of surgery. Propensity score matching method was used to match cases with and without complications. We used generalized gamma regressions to estimate the direct medical costs; logistic regressions to evaluate the impact of postoperative respiratory complications on re-hospitalization and outpatient visits. FINDINGS: Postoperative respiratory complications increased the odds of re-hospitalization and outpatient visits by 3·49 times (95% CI: 3·35–3·64) and 1·39 times (95% CI: 1·34–1·45) among surgical patients, respectively. The mean incremental cost associated with postoperative respiratory complications occurring within 30 days of the index admission was 1053·3 USD (95% CI: 940·7–1165·8) per procedure, which was equivalent to 41% of the GDP per capita of Vietnam in 2018. We estimated the national annual incremental cost due to respiratory complications occurring within 30 days after surgery was 13·87 million USD. Pneumonia contributed the greatest part of the annual cost burden of postoperative respiratory complications. INTERPRETATION: The economic burden of postoperative respiratory complications is substantial at both individual and national levels. Postoperative respiratory complications also increase the odds of re-hospitalization and outpatient visits and increase the length of hospital stay among surgical patients. FUNDING: The authors did not receive any funds for conducting this study